The effectiveness of “PEKA BERAKSI” programs in improving self-efficacy to prevent the risky sexual behavior in adolescents - Valen Fridolin Simak; Etty Rekawaty; Dwi Cahya Rahmadiyah (International Journal of Public Health Science (IJPHS), 2022)
Risky sexual behavior is a health problem among adolescents whose cases continue to increase along with technological developments. It needs to be overcome by increasing self-efficacy among adolescents. The purpose of this study was to provide an overview and influence of the implementation of “PEKA BERAKSI” on self-efficacy in adolescents to prevent risky sexual behavior. This study used quasi-experimental design with pre and posttest without control group method. The study involved 275 students. The instrument used to measure the variables of self-efficacy was measured with the instrument developed by researchers. The variable risky sexual behaviour was measured with the instrument sexual risk survey. The finding showed that there was a significant difference in self-efficacy in adolescents in preventing risky sexual behavior before and after the intervention 0.001. The results of statistical tests found a p-value of 0.006 which means that there is a significant effect between the “PEKA BERAKSI” intervention and risky sexual behavior. Based on these results, recommended for health services to make the innovation program that focuses health education for adolescents and health promotion at schools. Furthermore, the results of this intervention as basic data in developing school health clinics and integrating subjects with health education for adolescents.